STUDI KOMPERATIF KINERJA BANK UMUM SYARIAH DAN BANK KONVENSIONAL (Studi Kasus Bank Syariah dan Bank Konvensional yang terdaftar di OJK tahun 2023) - Khairani, Khairani (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to analyze the comparison of financial performance of conventional banks and Islamic banks. The population used in this study were 10 conventional banks and Islamic banks registered with the Financial Services Authority (OJK). The type of data used in this study is quantitative data and data analysis using the SPSS 25 application. The methods used are descriptive statistical analysis, independent sample t-test and mann whitney test. The results of this study indicate that there are significant differences that can be identified between the financial performance of conventional banks and Islamic banks in the CAR, and NPL variables, while in the ROA, and LDR variables there is no difference.